2018
DOI: 10.21303/2585-6847.2018.00768
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the radiation safety of the rural population of the Central Forest-Steppe of Ukraine in the remote period after the Chernobyl catastrophe

Abstract: In Ukraine, as a result of the Chernobyl disaster, 2,218 villages and cities with a population of about 2.4 million residents were in the zone of radioactive contamination. Pollution has undergone almost the entire territory of Polesia and a significant part of the Forest-Steppe. The population living in radioactively contaminated areas receives an additional more natural dose level of external and internal exposure. External irradiation is due to the high content of 137Cs in soils, with the decay of which inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…While settling on the ground, 137 Cs accumulates in the upper soil layer and remains there for many years (Filipović-Vinceković et al, 1991). This is confirmed by studies of soil samples taken after Fukushima and Chernobyl (Hashimoto et al, 2012), although compared to the 1991 data, the level of soil contamination has decreased by half (Herasymenko et al, 2018).…”
Section: Food Contaminationmentioning
confidence: 87%
See 4 more Smart Citations
“…While settling on the ground, 137 Cs accumulates in the upper soil layer and remains there for many years (Filipović-Vinceković et al, 1991). This is confirmed by studies of soil samples taken after Fukushima and Chernobyl (Hashimoto et al, 2012), although compared to the 1991 data, the level of soil contamination has decreased by half (Herasymenko et al, 2018).…”
Section: Food Contaminationmentioning
confidence: 87%
“…Recent studies of the specific activity of 137 Cs and 90 Sr in vegetable crops grown in the territory of voluntary guaranteed resettlement and the territory of enhanced radiological control showed that the lowest 137 Cs activity in comparison with other vegetables was in potatoes, onions and cucumbers, in While in sweet peppers and zucchini the 137 Cs activity was twice as high, in carrots and tomatoes it was almost 4 times, in beets -almost 8 times, in beans -10 times. The lowest level of 90 Sr activity is in onions, in tomatoes and cucumberstwice as high, in sweet peppers -4 times higher, in potatoes and cabbage -almost 10 times higher (Herasymenko et al, 2018) In both territories, the activity of 137 Cs and 90 Sr was the highest in cow milk and pork meat. An interesting fact is that in the spring-summer period the activity of 137 Cs and 90 Sr in milk was two to three times higher than in the autumn-winter period (Herasymenko et al, 2018).…”
Section: Food Contaminationmentioning
confidence: 91%
See 3 more Smart Citations